Collaboration in Transition Assessment: School Psychologists and Special Educators Working Together to Improve Outcomes for Students With Disabilities. Issue 3 (2nd July 2016) - Kellems, Ryan O.; Springer, Ben; Wilkins, Melinda K.; Anderson, Caroline
Abstract : The ultimate goal for school psychologists, special education practitioners, and other professionals who work with adolescents with disabilities is to help students plan and prepare to transition from school to adult life with the skills and knowledge to live happy, productive, and fulfilling lives. This article describes how school psychologists can support special education practitioners in improving transitions for students with disabilities, introduces free resources, and recommends forms of additional training. School psychologists are well positioned to support special education practitioners in facilitating the transition assessment process by providing documentation of postschool accommodation needs as students exit the school system.